Modelling Consumption and Constructing Long-Term Baselines in Final Demand - Mun Ho; Wolfgang Britz; Ruth Delzeit; Florian Leblanc; Roberto Roson; Franziska Schuenemann; Matthias Weitzel (Journal of Global Economic Analysis, 2020)
Modelling and projecting consumption, investment and government demand by detailed commodities in CGE models poses many data and methodological challenges. We review the state of knowledge of modelling consumption of commodities (price and income elasticities and demographics), as well as the historical trends that we should be able to explain. We then discuss the current approaches taken in CGE models to project the trends in demand at various levels of commodity disaggregation. We examine the pros and cons of the various approaches to adjust parameters over time or using functions of time and suggest a research agenda to improve modelling and projection. We compare projections out to 2050 using LES, CES and AIDADS functions in the same CGE model to illustrate the size of the differences. In addition, we briefly discuss the allocation of total investment and government demand to individual commodities.
Keywords: D12; D58; 330; Consumption demand systems; Long-term baseline; CGE models